Architecture, water and well-being in Islamic culture and beyond - Samalavičius, Almantas Liudas (Journal of Architecture and Urbanism, 2022)
The article aims to reconsider the historical role, peculiarities, significance, and meaning of water in traditional Islamic culture and society. The emergence of long-lasting systems of water supply in the territories that eventually gave rise to Islamic culture resulted in elaborate aesthetics of water most commonly associated with the phenomenon of the Islamic garden. In a piece of what might be described as a generalist’s interest, the author of the article examines this phenomenon and aesthetics of Islamic garden from the point of view of the history of ideas and attempts to grasp its universal features, which contributed to the dissemination of the cultural phenomenon beyond the Islamic realm and hadan impetus on the development of water culture in post-medieval Western Europe, especially during the Renaissance and Baroque eras when encounters with some of the Islamic cultural phenomena became more common and lasting. It is suggested that it was specifically the water culture of Islam that had an impact upon Western imagination and cultural practices from the dawn of the modern era. The author claims that the legacy of Islamic culture in the field of water aesthetics can be applied and used today in various regions even if symbolism of water has largely given ways to other concerns, among them about the future of the environment.